Seroprevalence Dynamics of European Bat Lyssavirus Type 1 in a Multispecies Bat Colony - Marc López-Roig; Hervé Bourhy; Rachel Lavenir; Jordi Serra-Cobo (Viruses, 2014)
We report an active surveillance study of the occurrence of specific antibodies to European Bat Lyssavirus Type 1 (EBLV-1) in bat species, scarcely studied hitherto, that share the same refuge. From 2004 to 2012, 406 sera were obtained from nine bat species. Blood samples were subjected to a modified fluorescent antibody virus neutralization test to determine the antibody titer. EBLV-1-neutralizing antibodies were detected in six of the nine species analyzed (Pipistrellus pipistrellus, P. kuhlii, Hypsugo savii, Plecotus austriacus, Eptesicus serotinus and Tadarida teniotis). Among all bats sampled, female seroprevalence (20.21%, 95% CI: 14.78%–26.57%) was not significantly higher than the seroprevalence in males (15.02%, 95% CI: 10.51%–20.54%). The results showed that the inter-annual variation in the number of seropositive bats in T. teniotis and P. austriacus showed a peak in 2007 (>70% of EBLV-1 prevalence). However, significant differences were observed in the temporal patterns of the seroprevalence modeling of T. teniotis and P. austriacus. The behavioral ecology of these species involved could explain the different annual fluctuations in EBLV-1 seroprevalence.